PPARγ Ligand as a Promising Candidate for Colorectal Cancer Chemoprevention: A Pilot Study - Hirokazu Takahashi; Kunihiro Hosono; Takashi Uchiyama; Michiko Sugiyama; Eiji Sakai; Hiroki Endo; Shin Maeda; Katherine L. Schaefer; Hitoshi Nakagama; Atsushi Nakajima (PPAR Research)
Activating synthetic ligands for peroxisome proliferator-activated receptor gamma (PPARγ), such as pioglitazone, are commonly used to treat persons with diabetes mellitus with improvement of insulin resistance. Several reports have clearly demonstrated that PPARγ ligands could inhibit colorectal cancer cell growth and induce apoptosis. Meanwhile, aberrant crypt foci (ACF) have come to be established as a biomarker of the risk of CRC in azoxymethane-treated mice and rats. In humans, ACF can be detected using magnifying colonoscopy. Previously, CRC and adenoma were used as a target for chemopreventive agents, but it needs a long time to evaluate, however, ACF can be a surrogate marker of CRC even for a brief period. In this clinical study, we investigated the chemopreventive effect of pioglitazone on the development of human ACF as a surrogate marker of CRC. Twenty-nine patients were divided into two groups, 20 were in the endoscopically normal control group and 9 were in the pioglitazone (15 mg/day) group, and ACF and adenoma were examined before and after 1-month treatment. The number of ACF was significantly decreased (5.8±1.1 to 3.3±2.3) after 1 month of pioglitazone treatment, however, there was no significant change in the number of crypts/ACF or in the number and size of adenomas. Pioglitazone may have a clinical application as a cancer-preventive drug. This investigation is just a pilot study, therefore, further clinical studies are needed to show that the PPARγ ligand may be a promising candidate as a chemopreventive agent for colorectal carcinogenesis.